The publishing ecosystems of contemporary australian genre fiction. Issue 2 (4th May 2018) - Driscoll, Beth; Fletcher, Lisa; Wilkins, Kim; Carter, David
Abstract: The cultural and commercial operations of the publishing industry have been dramatically reshaped by digital technologies, yet little is known about how these effects are differentiated across sectors of the industry. This article analyses data about the production of Australian-authored fantasy, romance and crime fiction titles to explore the specific publishing ecosystems of different genres and the roles played by multinational, small press and self-publishing in each. First, we show that there has been across-the-board growth in each genre and for each type of publisher. Second, we argue that multinational publishing activity in these genres has been characterized by broad stability, punctuated by experimentation with genre-specific imprints for romance and fantasy titles. Third, we find that small presses make diverse contributions to genre ecosystems, able to both activate prestige and experiment with formats. Finally, we note the immense growth in self-publishing, particularly in romance, and argue that self-publishing now operates in tandem with traditional publishing to create hybridized publishing ecosystems - with greater potential to transform the traditional publishing model than e-books.